Sailing against the law tides: Implications of the 2018 Refugee Reception Reform in Small-medium Towns and Rural Areas in Italy - Magda Bolzoni; Davide Donatiello; Leila Giannetto (Comparative Population Studies (CPoS), 2022)
Over the past decade, asylum seekers and refugees arriving in Italy were accommodated in reception facilities located not only in large metropolitan centres but also in Small-medium Towns and Rural Areas (STRAs). Italy's reception system evolved quickly to face the peaks of asylum applications, especially in the 2015-2017 period. At the same time, the changes in Italy's reception policies were pushed by the increased polarisation in the asylum debate, which, in turn, has led to great heterogeneity in the development of reception practices. This paper argues that the reception-territory nexus is a critical dimension to focus on when investigating the implications connected to the arrival and establishment of asylum seekers and refugees. This appears particularly true in STRAs where the reception system provided new resources that, when well-managed, showed transformative potential, developing virtuous interconnections with the local territories and communities. These virtuous interconnections have, however, been affected by the continuous changes in reception policies and came to a critical juncture in 2018, when the so-called Security Decree entered into force. While further modifications are currently underway, such legislation profoundly affected the Italian reception system's functioning and working principles, creating new frictions and tensions among institutional actors and within the local governance of the reception system itself. We argue that the reform contributed to disrupting, both materially and symbolically, the previous virtuous combination of refugee inclusion and local development, especially in STRAs. Our situated qualitative analysis - carried out between 2019 and 2020 through discursive in-depth interviews - investigates the interconnections between territory and reception in three small to medium-sized towns and rural areas before and after this regulatory shift. It does so by introducing a novel analytic framework, focusing on symbolic and material aspects within and around reception. The analysis suggests that the stress and disruptions connected to the regulatory changes have had a negative impact on the internal organisation of the reception as well as on the refugees' inclusion and on the chances of local development.
urn:nbn:de:bib-cpos-2022-10en2
Keywords: 300; Migrant reception and local transformations; Asylum seekers and refugees; Italian asylum system; Dispersal policies; Material and symbolic dimensions